1985
DOI: 10.2307/2112226
|View full text |Cite
|
Sign up to set email alerts
|

From Idealism to Pragmatic Detachment: The Academic Performance of College Athletes

Abstract: The authors discuss how the subjects from this basketball program come to college optimistic and excited about college in general. The research finds that first and even second years are more active in the school's community, clubs, and organizations outside of their sport. These student athletes also have every intention to graduate but become less involved in the school community as well as less motivated academically over time. The authors take into account many factors that may influence athletes to drift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 25 publications
3
123
2
Order By: Relevance
“…When conditions are unfertile, some identities may never be expressed (Adler & Adler, 1985) and may even atrophy. In school, this is deleterious for those students who never feel comfortable enough to express a learning identity or never fully develop a robust sense of self as a learner.…”
Section: Identitymentioning
confidence: 99%
“…When conditions are unfertile, some identities may never be expressed (Adler & Adler, 1985) and may even atrophy. In school, this is deleterious for those students who never feel comfortable enough to express a learning identity or never fully develop a robust sense of self as a learner.…”
Section: Identitymentioning
confidence: 99%
“…In contrast, research that situates college athletes' behavior and motivation in interaction with socialization processes has the potential to recognize college athletes' agency, while also avoiding blaming the victim or absolving institutions of all responsibility for outcomes. Unfortunately, this research suggests that college athletes' college experiences often perpetuate academic failure (Adler & Adler, 1985, 1991, 1999Benson, 2000;Comeaux, & Harrison, 2007;Fountain & Finley, 2009). Research must continue to explore college athletes' academic experiences in order to discover best practices for encouraging academic success (Martin & Harris, 2006;Martin et al, 2010) and to uncover how even successful college athletes may be harmed or shortchanged within the current system (Oseguera, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Most research has found that university athletes obtain lower grades compared to non-athletes (Sack, 1987-88;Adler & Adler, 1985). However, there are other researchers (Henschen & Fry, 1884;Shapiro, 1984) who have obtained reverse findings, showing that university athletes achieved better mean grades compared to non-athletes, while the third group of researchers (Hanks & Eckland, 1976;Stuart, 1985) found no difference in the mean grade among university athletes and non-athletes.…”
Section: Problem Statementmentioning
confidence: 99%
“…Most universities aimed to produce students with good academic performance but the competitive nature of intercollegiate sports has resulted in an 'anti-intellectual' subculture (Adler & Adler, 1985), lower academic achievement among students athletes (Allen, 1997) and also over dependency on personal support from other people for better achievement in both academic and social environment (Sack, 1988). Adler & Adler (1985) suggest many university athletes are not ready and not interested in academic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation